APPLICATION OF THE SNOWBALL THROWING LEARNING MODEL TO IMPROVE K3LH LEARNING OUTCOMES AND INDUSTRIAL CULTURE - Koto, Indra; Pakpahan, Sartika Yulianti (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2024)
This research aims to find out whether the snowball throwing learning model can improve student learning outcomes in the Basic subjects of the Motorcycle Engineering and Business Skills Program at Setia Budi Binjai Vocational School, and is Classroom Action Research (PTK). The learning model applied in this research is the snowball throwing type cooperative learning model. The subjects of this research were students in class X TBSM I SMKS Budi Binjai for the 2023/2024 academic year, totaling 30 students. The sample selection technique uses a purposive sampling technique, which selects subjects based on the researcher's subjective decision, while the variables observed are student activity and learning outcomes. The data collection technique in this research uses tests, namely pretest and posttest. Data analysis was carried out using quantitative descriptive analysis. The research results showed that the application of the snowball throwing learning model could improve the learning outcomes of class Student learning outcomes increased by 0.43 from 0.27 (medium category) in the posttest in cycle I then increased by 0.70 (medium category) in the posttest in cycle II.